La Tectonique des Appalaches du Québec - Béland, Jacques (Geoscience Canada, 1974)
Summary From the papers presented at the Symposium it appears that the geology of the Quebec Appalachians has been subjected to considerable changes these last few years. Logan's line or fault is now spread flat under a series of nappes and slices that constitutes a huge allochthon that extends from the US border to the tip of Gaspé Peninsula and was shoved over a platform that extended much farther south than had been previously assumed- The asbestos-rich serpentinite belt of the Eastern Townships has become an ophiolite complex several kilometres thick, complete with pelagic siliceous sediments. It has been emplaced by obduction. Bordering breccias are seen as trench mélanges related to plate consumption. The Taconian orogeny, different in style and extension from the Acadian orogeny, is ascribed to a phase of contraction that climaxed in Middle Ordovician and ceased in Late Ordovician. The Acadian orogeny is an altogether different episode that is not easily tied up with the previous Ordovician diastrophism. It can hardly be fitted in the plate tectonics scheme. Late rift valley tectonism is invoked to explain the Late Paleozoic - Early Mesozoic successor basin of mostly continental deposits that centres on the Gulf of St. Lawrence but that the rifting extended later to the St. Lawrence valley, as has been infered from the normal faulting recognized in the valley, is not readily accepted. It appears that this faulting is the origin of the Cambro-Ordovician exogeosyncline that received the allochthon but that it ceased with the Taconian contraction.